Antiproliferative effect of mifepristone (RU486) on human neuroblastoma cells (SK-N-SH): in vitro and in vivo studies - Casulari,L.A. (2020)
RU486 (mifepristone), a glucocorticoid and progesterone receptor antagonist, has been reported to exert antiproliferative effects on tumor cells. Experiments were performed to analyze the effects of RU486 on the proliferation of the human neuroblastoma, both in vitro and in vivo, using the human neuroblastoma SK-N-SH cell line. The exposure in vitro of SK-N-SH cells to RU486 revealed a dose-dependent inhibition of 3H-thymidine incorporation due to a rapid but persistent inhibition of MAPKinase activity and ERK phosphorylation. A significant decrease of SK-N-SH cell number was evident after 3, 6, and 9 days of treatment (up to 40% inhibition), without evident cell death. The inhibitory effect exerted by RU486 was not reversed by the treatment of the cells with dexamethasone or progesterone. Moreover, RU486 induced a shift in SK-N-SH cell phenotypes, with an almost complete disappearance of the neuronal-like and a prevalence of the epithelial-like cell subtypes. Finally, the treatment with RU486 of nude mice carrying a SK-N-SH cell xenograft induced a strong inhibition (up to 80%) of tumor growth. These results indicated a clear effect of RU486 on the growth of SK-N-SH neuroblastoma cells that does not seem to be mediated through the classical steroid receptors. RU486 acted mainly on the more aggressive component of the SK-N-SH cell line and its effect in vivo was achieved at a concentration already used to inhibit oocyte implantation.